2015
DOI: 10.5649/jjphcs.41.139
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Factors Affecting the Frequency of Bringing the Drug Profile Book and of Using the Stickers in Patients Taking Antihypertensives

Abstract: A survey was conducted at five insurance pharmacies for four months to clarify how frequently patients taking antihypertensives brought the drug profile book to their pharmacy; how frequently they used stickers for the profile book; and the correlated factors thereof. Survey forms were distributed to patients taking antihypertensives. The main questions were: (1) Patient attributes, (2) Frequency of bringing the profile book to their pharmacy, (3) Frequency of using the stickers, (4) Whether the respondents kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…7) By the foregoing survey, we have already obtained the following results. Table 1 shows the patient attributes.…”
Section: Survey Period and Participantsmentioning
confidence: 87%
See 4 more Smart Citations
“…7) By the foregoing survey, we have already obtained the following results. Table 1 shows the patient attributes.…”
Section: Survey Period and Participantsmentioning
confidence: 87%
“…We already found that frequency of bringing the drug proˆle book and frequency of the sticker a‹x rose in line with the strength of the sense of utility of the drug proˆle book. 7) In this paper, alongside conˆrmation of a relationship between i) the sense of utility of the drug proˆle book and ii) frequency of bringing the drug proˆle book, frequency of the sticker a‹x, and experience of showing the drug proˆle book to the physician, it is conceivable that the patients' sense of the utility of the drug proˆle book were related to the fact that the pharmacist communicated via the drug proˆle book and by the fact that patients themselves had more opportunity to utilize the drug proˆle book and that this, in turn, led to the patients safely undertaking medication. It was reported that 92.3% of physicians successfully prevented duplicate medication that may have occurred among medical facilities by using the drug proˆle book 8) while another report indicated that only 44.3% of patients showed the drug proˆle book at clinics or hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations